2019
DOI: 10.5761/atcs.oa.18-00158
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Lung Cancer Inflammation Index Predicts Outcomes of Patients with Pathological Stage IA Lung Adenocarcinoma Following Surgical Resection

Abstract: Purpose: The correlation of advanced cancer with inflammation and/or nutrition factors is well known. Recently, the advanced lung cancer inflammation index (ALI) was developed as a new prognostic tool for patients with advanced lung cancer. In this study, we examined whether ALI results are correlated with prognosis of patients with early stage lung adenocarcinoma who undergo lung resection. Methods: From January 2009 to December 2014, 544 patients underwent lung resection due to primary lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 22 publications
(30 reference statements)
2
33
0
Order By: Relevance
“…Kobayashi et al examined the prognostic value of the ALI in lung adenocarcinoma patients and concluded that the ALI was an independent predictor of OS (HR = 7.55, 95% CI = 3.03-18.8) and had a better prognostic value than the NLR (HR = 3.91, 95% CI = 1. 36-11.26) and GPS (HR = 1.24, 95% CI = 0.32-4.77) [33]. Tomita et al revealed that the preoperative ALI and CRP levels were significant predictors of OS in patients with NSCLC and that the ALI (HR = 0.436, 95% CI = 0.278-0.679) was superior to the CRP level (HR = 0.631, 95% CI = 0.403-0.993) as a prognostic index [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kobayashi et al examined the prognostic value of the ALI in lung adenocarcinoma patients and concluded that the ALI was an independent predictor of OS (HR = 7.55, 95% CI = 3.03-18.8) and had a better prognostic value than the NLR (HR = 3.91, 95% CI = 1. 36-11.26) and GPS (HR = 1.24, 95% CI = 0.32-4.77) [33]. Tomita et al revealed that the preoperative ALI and CRP levels were significant predictors of OS in patients with NSCLC and that the ALI (HR = 0.436, 95% CI = 0.278-0.679) was superior to the CRP level (HR = 0.631, 95% CI = 0.403-0.993) as a prognostic index [56].…”
Section: Discussionmentioning
confidence: 99%
“…1. Ultimately, nine studies met our selection criteria; after excluding duplicated studies and reviewing the full texts of the manuscripts [25,[29][30][31][32][33][34][35][36], a total of 1736 cases were included. With respect to prognostic outcomes, nine studies reported OS, two studies reported progression-free survival, and one study reported disease-free survival.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The PLR is determined by the platelet count divided by the lymphocyte count. Finally, the GPS combines an inflammatory parameter (CRP) and a nutritional factor (albumin): patients are assigned 1 point if they have a CRP level >10 mg/L or hypoalbuminemia (<3.5 g/dL), and they are finally classified into groups with 0, 1, or 2 points [20].…”
Section: Methodsmentioning
confidence: 99%
“…While the ICD-O-3 codes are particularly important for PCa cases, the importance of additional benign findings is especially important for inflammation and hypertrophy that have been shown to be linked with many other cancers. 39 , 40 Several studies have indicated that chronic inflammation has a potential role in prostatic carcinogenesis and tumour progression. 39 , 41 , 42 Nelson et al reported that chronic or recurrent inflammation may play a role in the development of PCa.…”
Section: Discussionmentioning
confidence: 99%